Structural performance and associated lessons to be learned from world earthquakes in Nepal after 25 April 2015 (MW 7.8) Gorkha earthquake. (October 2016) - Gautam, Dipendra; Chaulagain, Hemchandra
Abstract: Gorkha earthquake (MW 7.8) occurred in Nepal on 25 April 2015 at 11:56 local time. This earthquake is the most devastating event after the 1934 great Bihar-Nepal earthquake (MW 8.1) in terms of damages. In that earthquake, 498, 852 buildings were completely collapsed and other 256, 697 were partially damaged. Structural and non-structural damages were occurred in all types of prevalent structural systems in affected areas. This paper outlines the structural performance during Turkey, Bhuj, Kashmir, Haiti, Chile and L'Aquila earthquakes from past two decades worldwide and comparisons are made in terms of structural forms, regulations to infer the lessons to be learnt by Nepal in the aftermath of Gorkha earthquake. Apart from this, review of structural performance during two major earthquakes of 1934 (MW 8.1) and 1988 (MW 6.5) in Nepal is presented to draw insights in terms of changing structural forms, technology and housing units. Insights are presented in terms of codal provisions and distribution of structures in Nepal. With due account of major world earthquake paradigms and historical earthquakes from Nepal and detailed field reconnaissance after the Gorkha earthquake, interpretations are disseminated in terms of lessons to be learned by Nepal in the aftermath of Gorkha earthquake. Comparative analyses have highlighted the urgent need of building code revision and development of proper strengthening techniques for the affected structures. Highlights: Structural performance during 2015 Gorkha earthquake is disseminated. Structural performance during past earthquakes in Nepal is outlined. Comparative analysis of damages during major world earthquakes is discussed. Lessons to be learned in the aftermath of Gorkha earthquake are formulated. Critical review of building regulations in Nepal is presented.